Pressure Drop Correlation Covering Dilute to Dense Regimes of Solid Particle-Gas Flow in a Vertical Conveying Pipe - Bindar, Yazid; Sutrisniningrum, N. A.; Santiani, D. (ITB Journal Publisher, LPPM ITB, 2009)
More general correlations between pressure drop and gas-solid flow variables are developed from the present experimental data. The correlation was modeled for a pneumatic conveying system in a vertical pipe. The transition boundary between dense and dilute regimes is constructed from the pressure drop correlations. The gas-solid particle flow variables are quantified by the gas Reynolds (Nref) and the solid Froude (Frp) numbers. The dense flow regime is indicated by the decrease of the pressure drop with the increase of the gas Reynolds number. In contrary, the dilute regime exhibits the increase of the pressure drop with the gas Reynolds number. The proposed correlations were built at the range of gas Reynolds number f from 360 to 500 and solid Froude number from 0,01 to 0,02.